STUDIES ON 5-CYANOURACILS: EXPEDIENT SYNTHETIC PROTOCOL FOR SYNTHESIS OF NOVEL PYRIDO[2,3-d]PYRIMIDINE AND PYRIMIDO [4,5-d]PYRIMIDINE ANALOGS WITH POTENTIAL PHARMACOLOGICAL ACTIVITY - YOGESH Y. PEDGAONKAR; ARUNDHATI C. LELE; NUTAN H. PALSULE DESAI; MARIAM S. DEGANI (International Journal of Pharma and Bio Sciences, 2014)
Novel, diverse pyrido [2,3-d] pyrimidine and pyrimido [4,5-d] pyrimidine analogs were synthesized by the reaction of 1,3-substituted-5-cyano uracil derivatives with appropriate nucleophile under mild conditions. Utilising 5-cyano uracil with various substitutions as a substrate leads to rapid synthesis of annulated uracils with diverse biological properties.